Screening of rhizosphere soil bacteria for biocontrol of Lasiodiplodia theobromae - Chukeatirote, Ekachai; Phueaouan, Thanong; Piwkam, Anong (Agriculture and Natural Resources, 2018)
Rhizobacteria capable of inhibiting Lasiodiplodia theobromae were screened. In total, 890 rhizobacterial strains were isolated and initially screened for their antagonistic activity using a dual culture test, resulting in 149 isolates being able to inhibit the fungal growth. The antagonistic activity was then rechecked using the culture supernatant. In this step, there were 78 bacterial isolates yielding supernatant that could inhibit the fungal growth. Of these, the isolate named JN15 showed maximum inhibition of the fungus L. theobromae (approximately 60%). The antifungal activity of the JN15 culture supernatant was stable in the pH range 4-10 (29-42% inhibition) and remained active at 40 °C. The bacterial strain JN15 isolated from Senna siamea was then characterized in terms of its phenotypic and genotypic properties including morphology, biochemical profiles, and 16S rRNA gene sequence. Based on this analysis, the bacterium JN15 was identified as Bacillus amyloliquefaciens.